Project management, planning and control managing engineering, construction, and manufacturing projects to PMI, APM, and BSI standards - Lester, Albert (Butterworth-Heinemann Elsevier, 2014)
Covering the principles and techniques you need to successfully manage an engineering or technical project from start to finish, Project Management, Planning and Control is an established and widely recommended project management handbook. With clear and detailed coverage of planning, scheduling and control, which can pose particular challenges in engineering environments, this sixth edition includes new chapters on Agile project management and project governance, more real-life examples and updated software information. Ideal for those studying for Project Management Professional (PMP) qualifications, Project Management, Planning and Control is aligned with the latest Project Management Body of Knowledge (PMBOK) for both the Project Management Institute (PMI) and the Association of Project Management (APM), and includes questions and answers to help you test your understanding. It is also updated to match the latest BS 6079 standard for project management in construction.